Validity and Reliability of the Tromso Social Intelligence Scale (TSIS): A Study of Malaysian Teachers - Zaine Zulkifli; Intan Hashimah Mohd Hashim; Mahathir Yahaya (Journal of Human Development and Communication (JoHDeC), 2025)
The purpose of this research was to investigate the validity and reliability of the Tromo Social Intelligence Scale (TSIS). The survey included 357 secondary school teachers from the state of Pahang. Tromso Social Intelligence Scale has 21 items with three subscales: social awareness, social skills, and social information processing. Factor analysis and Cronbach’s Alpha were used to examine validity and reliability. The results of principal component analysis with Promax rotation and scree plot retrieved four factors that contributed 60.37 percent of the total variance and provided loadings ranging from 0.354 to 0.735. However, the 4-factor created by the analysis did not correspond to any of the factors proposed in the prior study, yielding new unknown 4 factors. It was suggested that more research be done to corroborate the study’s psychometric features.